THE POTENCY OF BAJAKAH TAMPALA (Spatholobus littoralis Hassk) AN INDIGENOUS INDONESIAN HERBAL MEDICINE : A BIBLIOMETRIC APPROACH - Davit Nugraha; Nurkhasanah; Sapto Yuliani (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Bajakah tampala (Spatholobus littoralis Hassk) has significant potential in the pharmaceutical field and could become a source for drug discovery and development in the future. This bibliometric analysis aimed to map existing research to identify novelties and gaps for future studies. The research method involved a literature review using bibliometric analysis, using the keyword